Working More to Pay the Mortgage: Household Debt, Interest Rates, and Family Labor Supply - Zator, Michał (Journal of Finance, 2025)
ABSTRACT I show that households work and earn more (less) when their floating‐rate mortgage payments quasi‐exogenously increase (decrease). The response is sizable and asymmetric: on average, households adjust their income by 35% of the change in their mortgage payment, but the response is significantly stronger following an increase in payments. While men in dual‐earner, childless households respond the most on average, the asymmetry is most pronounced for women and young workers, who respond particularly strongly to payment increases. The asymmetry of the labor supply elasticity may help explain the wide range of elasticities found in previous research.